Can tax knowledge, trust in government and perceived tax fairness encourage tax compliance? - Dahniyar Daud; Nuramal Nuramal (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2026)
Purpose – This study examines whether tax knowledge, trust in government, and tax fairness influence tax compliance among small and medium enterprises (SMEs) the Makassar City area.Methodology –Using a survey-based approach, we sampled 260 SMEs operating in Makassar City, Indonesia. Data were analyzed using Partial Least Squares (PLS) modeling techniques.Findings – Our empirical results indicate that tax knowledge does not significantly contribute to tax compliance, whereas tax fairness shows a significant effect. In the model, tax fairness significantly mediates the relationship between tax knowledge and tax compliance. Furthermore, trust in government significantly influences both tax compliance and tax fairness. Additionally, tax fairness plays a significant mediating role in the relationship between trust in government and tax compliance.Originality/Novelty –In light of this, our study is the first to examine tax fairness as a mediating variable in the relationship between tax knowledge and trust in government, and tax compliance, specifically within the Indonesian context.Implications – Our findings provide important theoretical evidence that when SME actors perceive transparency from government officials in tax-related matters, it fosters both awareness and a genuine intention to pay taxes. This trust contributes to the perception of tax fairness, ultimately leading to improved tax compliance.